Identifying Code Clones with RefactorErl - Fördős, Viktória; Tóth, Melinda (Acta Cybernetica, 2016)
Code clones, the results of "copy&paste programming", have a negative impact on software maintenance. Therefore several tools and techniques have been developed to identify them in the source code. Most of them concentrate on imperative, well known languages, while in this paper, we give an AST/metric based clone detection algorithm for the functional programming language Erlang. We propose a standalone solution that does not overload users with results that are insignificant from the point of view of the user. We emphasise that the maintenance costs can be decreased by using our solution, because the programmers need to deal only with important issues.